Empowering engagement: unveiling motivational drivers for social media adoption: a Facebook case study - Allam, Hesham; Dempere, Juan; Lazaros, Edward J.; Davison, Chris (Frontiers in Computer Science, 2024)
Introduction Social networking websites and applications are increasingly becoming significant cultural phenomena. However, the motivation driving individuals to utilize these platforms, particularly in the Middle East, remains unclear. While numerous studies have explored technology adoption, limited research has investigated social media usage in the UAE. Therefore, this study proposes and empirically analyzes a framework based on a modified version of the Technology Acceptance Model to understand the factors influencing users’ opinions, objectives, and actual usage of social media platforms, focusing on Facebook. Methods To investigate these factors, we employed structural equation modeling and smart PLS techniques on a sample of 540 participants. We aimed to identify predictors such as perceived usefulness, perceived ease of use, as well as a hedonic dimension encompassing perceived enjoyment, curiosity, and perceived connectedness, in shaping users’ attitudes towards Facebook usage. Additionally, we examined the relationship between social presence and users’ intentions to use Facebook. Results Our analysis revealed that perceived usefulness and perceived ease of use are significant predictors of users’ attitudes towards utilizing Facebook. Furthermore, the hedonic dimension, comprising perceived enjoyment, curiosity, and perceived connectedness, also plays a crucial role in shaping users’ attitudes. Moreover, social presence was found to have a significant association with users’ intentions to use Facebook. Discussion These findings contribute to our understanding of the factors influencing the adoption and usage of social media platforms, particularly in the context of the UAE. By highlighting the importance of both utilitarian and hedonic aspects, this research provides insights into the complex motivations behind individuals’ acceptance of dynamic applications like Facebook. Furthermore, our empirical model lays the groundwork for exploring additional factors that may influence the uptake of information systems and social media utilities, thereby advancing attitude-behavior theories in this domain.